2022
DOI: 10.1111/jfpp.16977
|View full text |Cite
|
Sign up to set email alerts
|

Wheat bran enrichment for flour products: Challenges and solutions

Abstract: Wheat bran (WB) is a major by‐product of wheat processing and is widely used as livestock feed and brewing material. Its development and application have attracted a great deal of interest in both scientific and industrial domains due to the increasing demand for more healthy foods. Hence, using WB‐added flours is seen as an effective means of improving the nutritional quality of flour products. However, the high insoluble dietary fiber content of WB may affect the quality of flour products during processing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 105 publications
0
6
0
Order By: Relevance
“…The free, bound, and total flavonoid contents of BWBGN, WWBGN, and EWBGN were significantly decreased compared to that of UWBGN ( P < 0.05). Yan et al 45 . indicated that double‐pass extrusion was more effective in releasing ferulic acid and improved the bio‐accessibility of bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free, bound, and total flavonoid contents of BWBGN, WWBGN, and EWBGN were significantly decreased compared to that of UWBGN ( P < 0.05). Yan et al 45 . indicated that double‐pass extrusion was more effective in releasing ferulic acid and improved the bio‐accessibility of bioactive compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The free, bound, and total flavonoid contents of BWBGN, WWBGN, and EWBGN were significantly decreased compared to that of UWBGN (P < 0.05). Yan et al 45 indicated that double-pass extrusion was more effective in releasing ferulic acid and improved the bio-accessibility of bioactive compounds. A possible explanation for this phenomenon was that flavonoids are more sensitive to heating than phenolic and decreased during cooking.…”
Section: Effects Of Three Thermal Treatments On Antioxidant Activitymentioning
confidence: 99%
“…Alkali treatment increases SDF and improves bile acid-binding capacity, WHC, α-amylase activity, GAC, WSC, and thermal stability. A coupled acid-alkaline treatment had the most significant results on improving fibre solubility [24,282,283].…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…There have been different attempts to reduce or eliminate these negative effects including reducing the bran size (Cai et al., 2014; Cingöz et al., 2023; Kaprelyants et al., 2013; Noort et al., 2010), using enzymes (Yan et al., 2022), addition of vital gluten (Messia et al., 2016; Ortolan & Steel, 2017), fermentation (Hemdane et al., 2016), extrusion (Gomez et al., 2011), and hydrothermal treatment of wheat bran (Cingöz et al., 2023; Kabel et al., 2007). Some enzymes including α‐amylases (Liu et al., 2017), xylanase (Yan et al., 2022), cellulase (Park et al., 2018), lipase (Melis et al., 2019), dextransucrase (Kajala et al., 2015), protease (Fuentes et al., 2016), oxidative enzymes (Fuentes et al., 2016) affect dough stability and bread shelf life positively and reduce the rate of staling and thus prolong bread freshness. Fermentation of bran changes the cell wall structure by converting arabinoxylans into a soluble form and thus overcomes its negative effects on dough and bread.…”
Section: Introductionmentioning
confidence: 99%